How to safeguard groundwater resources in Jerba Island in the scenario of a sea level rise using 3D-FEFLOW salinity transport model? - Collignon, Bernard; Lachaal, Fethi; Hedoin, Jérémie (2019)
The groundwater resources in Jerba Island are especially sensitive to sea level rise (SLR) because the island's relief is very moderate and the altitude of the piezometric surface is close to zero. Sea water intrusion is widespread but varies from one area to another, depending on groundwater abstraction rate and economic activities. The freshwater lens is probably sustained in the eastern part of the island through the infiltration of some wastewater. To meet the expected demand growth, integrated management of all water resources will be paramount (including irrigation quotas, infiltration of treated wastewater and desalination of brackish water). In this study, we numerically investigate the impact of SLR by the implement of a 3D- FEFLOW salinity transport model for the costal aquifer in Jerba Island. The model was calibrated and validated with datasets during the 1992–2018 period. The water table and salt intrusion evolutions were estimated according multiple scenarios of climate change (8.5 and 4.5). The groundwater recharge, extraction, discharge into the aquifer, rainfall, and water need were projected according the same scenarios. For each scenario, the piezometric and salinity maps were simulated for the years 2030, 2050, and 2100. The model simulations show that the Jerba aquifer exhibits a highest sensibility to SRL and intensive extraction. The model is an essential tool for organizing a sustainable groundwater management, with the aim of preserving the agricultural and tourist activities that form the basis of the island's economy. It can be regarded as a useful tool for analyzing the water resources management and sea water intrusion for groundwater in arid and semi-arid regions and will help to propose a management rescue plan for aquifer remediation.
Keywords: Géologie – Djerba

Geochemical and statistical studies of Mio-Pliocene aquifer's mineralization in Jerba Island, South-eastern Tunisia - Farhat, Soumaya; Bali, Mahmoud; Kamel, Fethi (Physics and Chemistry of the Earth, Parts A/B/C, 2019)
Keywords: Géologie – Djerba